Public–private partnerships and physical activity: a matter of health promotion and chronic disease prevention - Pires, Gabriel Natan; Roger-Silva, Diego (Clinical and Biomedical Research, 2021)
Public–private partnerships are joint initiatives between the public and private sectors with a specific focus and a defined level of action. Several international reports have shown good results of public–private partnerships using physical activity interventions associated with public health policies and strategies. Among these reports, we highlight those that focus on the prevention of chronic diseases such as cardiovascular disease, diabetes, asthma, and obesity using physical activity as the main tool. This article discusses the conceptual framework behind these partnerships, addressing their possible effectiveness and feasibility. We debate important factors in the success of these partnerships, as well as possible benefits to the public and private entities involved and to the target populations of these interventions.